Protocol: In-person Interventions To Reduce Social Isolation And Loneliness: An Evidence And Gap Map - Vivian Welch; Elizabeth Tanjong Ghogomu; Sierra Dowling; Wan Yuen Choo; Raudah M. Yunus; Tengku A. M. Tengku Mohd; Niobe Haitas; Sivan Bomze; Simone Dahrouge; Edward Garcia; Julianne Holt‐Lunstad; Mathias Lasgaard; et al. (John Wiley & Sons Inc., 2024)
Indexed by WOS/Scopus/ERA